2019
DOI: 10.32996/ijllt.v2i5.618
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Using Authentic Texts on Iranian EFL Learners' Incidental Vocabulary Learning: The Case of English Newspaper

Abstract: This study intended to investigate the effect of using authentic texts on Iranian EFL learners' incidental vocabulary learning. To this end, a population of 52 Iranian female EFL learners aged 15 to 17 was selected. They were two intact classes; experimental group (25 students) and control group (27 students). Both groups received a pretest at the first session. Regarding the treatment, the authentic reading texts selected from World News for students of English, Level1 was taught to the experimental group whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 16 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…It is suggested that students acquire new vocabulary when exposed to unfamiliar words in contexts when reading an authentic text. It is claimed that this compensates for the impracticality of teaching every word explicitly in the classroom (Shakibaei et al, 2019). It is paralleled with the findings of prior research that showed learners' exposure to English media, such as video games, websites, and TV series is a better predictor of their vocabulary size than formal schooling (Cetinkaya, 2021).…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…It is suggested that students acquire new vocabulary when exposed to unfamiliar words in contexts when reading an authentic text. It is claimed that this compensates for the impracticality of teaching every word explicitly in the classroom (Shakibaei et al, 2019). It is paralleled with the findings of prior research that showed learners' exposure to English media, such as video games, websites, and TV series is a better predictor of their vocabulary size than formal schooling (Cetinkaya, 2021).…”
Section: Introductionmentioning
confidence: 70%
“…On the other hand, authentic texts are lexically richer and therefore are regarded as excellent resources for vocabulary acquisition. It increases the tendency of incidental vocabulary learning (Shakibaei et al, 2019). It is suggested that students acquire new vocabulary when exposed to unfamiliar words in contexts when reading an authentic text.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that students achieved significant gains in vocabulary through television viewing and frequency of word occurrence played a substantial role in the relationship. Other studies have associated significant improvement in vocabulary through listening to songs (Pavia et al, 2019), reading newspapers (Shakibaei et al, 2019), and recreational reading (Malone, 2018). In second language learning, vocabulary knowledge is predictive of a learner's success in performing language skills.…”
Section: Vocabulary Knowledgementioning
confidence: 99%
“…Teachers control the process and teaching content, while students follow teachers to complete the learning of the content. Such a teaching approach has been confirmed to be ineffective for practical-based courses; students are not able to control their learning pace (Shakibaei et al, 2019); they can passively accept the learning process in which the teacher dominates. Using traditional methods in information and communications technology (ICT) courses gives limited time for practical activities, leading to inadequate students' ICT skills, learning achievement, and self-efficacy (Samaila et al, 2022).…”
Section: Introductionmentioning
confidence: 99%